2015
DOI: 10.1097/md.0000000000002413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Sleep Disordered Breathing in Fabry disease

Abstract: Excessive daytime sleepiness (EDS) is a frequently reported and not well-understood symptom in patients with Fabry disease (FD). Sleep-disordered breathing (SDB) is a possible factor. As deposition of glycosphingolipids in the upper airway muscles is likely, we hypothesized that obstructive sleep apnoea (OSA) is highly prevalent in FD and positively associated with its severity.All patients with FD who are followed in the Fabry cohort of the University Hospital Zurich (n = 62) were asked to participate in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 36 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…However, direct damage from deposits in other cell types may also contribute to organ dysfunction, such as e.g. airways and lung [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, direct damage from deposits in other cell types may also contribute to organ dysfunction, such as e.g. airways and lung [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Franzen et al performed a PSG and assessed daytime sleepiness and disease severity through the Epworth Sleepiness Scale and Mainz Severity Score Index, respectively, on 52 patients with Fabry disease. The authors found that 13 patients (25%) had SDB (78% OSA and 22% central sleep apneas) [84]. Talbot et al also observed SDB in 10 out of 20 patients with Fabry disease who underwent a PSG [85].…”
Section: Fabry Diseasementioning
confidence: 99%
“…Her history was negative for the 4 pain phenotypes of Fabry disease (pain attacks, pain crises, evoked pain/hyperalgesia, and chronic pain) 1,11 and obstructive sleep apnea. 3 General anesthesia for both surgeries consisted of induction with fentanyl 3 μg/kg IV, propofol target-controlled infusion (TCI) 8 μg/mL IV, and rocuronium 0.6 mg/kg IV; maintenance with propofol and remifentanil TCI; and additional analgesia with paracetamol, metamizole, and fentanyl IV. A lidocaine infusion was added to the maintenance regiment for the longer second surgery.…”
Section: Patientmentioning
confidence: 99%
“…The widely variable clinical picture includes acroparesthesia, cornea verticillata, and abdominal pain in childhood; angiokeratoma, renal insufficiency, and electrocardiographic abnormalities in adolescence; and excessive daytime sleepiness, obstructive sleep apnea, hypertension, cardiomyopathy, renal failure, and stroke in adults. [1][2][3] General anesthesia has been described in only 4 patients. [4][5][6] We present 2 female patients with Fabry disease who required general anesthesia twice for gynecological and trauma surgery, respectively, and discuss their perioperative management based on the explosion of new information in the medical literature.…”
mentioning
confidence: 99%